Profiling TRA-1-81 antigen distribution on a human embryonic stem cell - Qiu, Dengli (2008)
Human embryonic stem (hES) cells hold great promise in regenerative medicine. Although hES cells have unlimited self-renewal potential, they tend to differentiate spontaneously in culture. TRA-1-81 is a biomarker of undifferentiated hES cells. Quantitative characterization of TRA-1-81 expression level in a single cell helps capture the “turn-on” signal and understand the mechanism of early differentiation. Here we report on our examination of TRA-1-81 distribution and association on a hES cell membrane using an atomic force microscope (AFM). Our results suggest that aggregated distribution of TRA-1-81 antigen is characteristic for undifferentiated hES cells. We also evaluated the TRA-1-81 expression level at ~17800 epitopes and ~700 epitopes per cell on an undifferentiated cell and a spontaneously differentiated cell, respectively. The method in this study can be adapted in examining other surface proteins on various cell types, thus providing a general tool for investigating protein distribution and association at the single cell level.